No association between gingival labial recession and facial type - Mazurova, Katerina; Renkema, Anne-Marie; Navratilova, Zuzana; Katsaros, Christos; Fudalej, Piotr S (European journal of orthodontics, 2016)
OBJECTIVE: To evaluate if facial type is a predictor of the development of gingival recession. METHODS: A cohort of 179 orthodontic patients (76 males, 101 females; age before treatment T S = 12.4 years, SD = 0.8) were followed until 5 years post-treatment (T 5 = 20.7 years, SD = 1.2). The presence of recessions was scored ('Yes' or 'No') by two raters on initial (T S), end of treatment (T 0), and post-treatment (T 5) plaster models. A recession was noted (scored 'Yes') if the labial cemento-enamel junction was exposed. The clinical crown heights were measured at T S, T 0, and T 5 as the distances between the incisal edges and the deepest points of the curvature of the vestibulo-gingival margins. Determination of the facial type was based on the inclination of mandibular plane relative to cranial base (Sella-Nasion/Mandibular Plane) and the proportion of posterior to anterior face heights (PFHs; SGo/NMe × 100 per cent) on pre-treatment cephalograms. RESULTS: From T 0 to T 5, the number of subjects with recessions increased from 2 (1.1 per cent) to 24 (13.6 per cent), and the number of recession sites increased from 2 to 39. However, most patients had either one or two recession sites. The mean clinical crown height of mandibular incisors increased by 0.86mm (SD = 0.82, P < 0.001). Regression analysis showed that mandibular plane inclination had no effect on the development of gingival recession or on the increase of clinical crown heights of mandibular incisors. CONCLUSIONS: Facial type is not a predictor of the occurrence of gingival recession.
Keywords: kohortové studie; Incisor; Humans; Child; Adolescent; mandibula; Gingival Recession; kefalometrie; Radiography, Dental; prognóza; Orthodontics, Corrective; lidé; dítě; ústup dásní; Mandible; obličejové kosti; Female; Cohort Studies; Regression Analysis; Cephalometry; Prognosis; rizikové faktory; Male; rentgendiagnostika zubní; mladiství; regresní analýza; následné studie; Follow-Up Studies; Risk Factors; Facial Bones; ortodoncie korekční; řezáky; ženské pohlaví; mužské pohlaví; zubní krček; Tooth Cervix